Cornus officinalis kernel porous carbon as well as preparation method and application thereof
By controlling the carbonization and pore formation parameters, the porous carbon of the Cornus core with moderate pore size was prepared and used for the silicon negative electrode of lithium batteries, which solved the problem of insufficient electrochemical performance caused by the many micropores in the existing technology, and improved the energy density of lithium batteries and Cyclic stability.
Patent Information
- Application Number
- CN202411341541.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
AI Technical Summary
The existing cornus fruit core activated carbon has a large number of micropores and is not suitable for silicon negative electrodes of lithium batteries. It has insufficient electrochemical performance and stability.
By controlling the parameters of carbonization and pore formation, porous carbon from Cornus core with moderate pore size was prepared. The number of mesoporous and macropores was large and the number of micropores was small. It was used as the skeleton material for lithium battery silicon negative electrodes, loaded with nanosilicon, and acidified by Treatment regulates surface properties to improve performance.
The energy density of lithium batteries is increased by about 1-2 times, enhancing the wrapping performance and structural stability of nano-silicon, reducing the expansion rate, and improving cycling stability.
Smart Images

Figure CN119191292A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biochar, and in particular to a porous charcoal made from a cornus fruit core, a preparation method and an application thereof. Background Art
[0002] Cornus officinalis is a small tree or shrub belonging to the genus Cornus in the family Cornaceae. Its mature fruit is also known as cornus flesh, medicinal jujube, jujube peel, etc. after the pit is removed. Cornus officinalis is distributed in the northern temperate zone and subtropical high mountainous areas. It is mainly produced in China, Japan, South Korea, the United Kingdom, the United States and other countries.
[0003] At present, there are more studies on the pulp of Cornus officinalis, but relatively few studies on the utilization of its kernels. The weight of the dried kernels of Cornus officinalis is about 1 / 3 of the pulp. If a large number of hard kernels are not effectively utilized, precious biomass resources will be wasted.
[0004] Compared with activated carbon, porous carbon has a structure dominated by mesopores and macropores, with relatively few micropores. Therefore, porous carbon has a relatively high pore volume, is more suitable for the deposition of silane gas, has good electrochemical performance and stability, and is suitable for energy storage fields such as batteries and supercapacitors. Patent CN106395818A discloses a method for preparing activated carbon from cornus fruit cores, which can obtain an activated carbon after drying, acidification, and high-temperature treatment at 550°C. The activated carbon can be used in the adsorption field, but the activated carbon has a large number of micropores and is not suitable for lithium battery silicon negative electrodes. Its electrochemical performance and stability are poor. Summary of the invention
[0005] The purpose of the present invention is to provide a porous carbon from cornus fruit core, which has a small number of micropores and is mainly composed of mesopores and macropores, and can be used for silicon negative electrodes of lithium batteries.
[0006] Another object of the present invention is to provide a method for preparing porous carbon from Cornus officinalis fruit core, by controlling the pore size of the porous carbon by controlling the parameters of carbonization and pore formation, the porous carbon formed has a moderate pore size, a large number of mesopores and macropores, a small number of micropores; and the pore size distribution is uniform.
[0007] The third purpose of the present invention is to provide an application of porous carbon from Cornus officinalis fruit core in the preparation of lithium battery negative electrode, with the porous carbon as the skeleton material and loaded with nano-silicon. The porous carbon has a strong ability to load nano-silicon and has good wrapping performance for nano-silicon. The nano-silicon is not easy to fall off, which can increase the energy density of the lithium battery by about 1-2 times.
[0008] The present invention solves the technical problem by adopting the following technical solutions.
[0009] On the one hand, an embodiment of the present invention provides a method for preparing a porous carbon from a cornus fruit core, comprising the following steps:
[0010] S1, drying the washed cornus fruit pits at 105° C.-130° C., and then putting them into a carbonization furnace for carbonization to obtain a carbonized cornus fruit pit material;
[0011] S2, crushing and grinding the carbonized material of Cornus officinalis kernel obtained in step S1 to obtain carbon powder;
[0012] S3, placing the carbon powder in step S2 into a mixture of solid potassium hydroxide and solid sodium hydroxide, stirring evenly to obtain a mixture;
[0013] S4, placing the mixture of step S3 in an activation furnace for activation and pore formation to obtain an activated material;
[0014] S5, placing the activated material in step S4 in a mixed acid solution, heating it for acidification reaction, and then filtering, washing the filter residue, drying it, and demagnetizing it.
[0015] In some embodiments of the present invention, in step S1, the carbonization conditions are: in a nitrogen atmosphere, the heating rate is 2-5°C / min, and the temperature is kept at 300°C-600°C for 3-5h. Under the carbonization conditions, not only can the cornus fruit core be fully carbonized to make the pore size distribution uniform, but also the loss of carbon element can be reduced, and the cornus fruit core can be fully utilized to improve its utilization efficiency.
[0016] In some embodiments of the present invention, in step S3, the mass ratio is, carbon powder: total amount of potassium hydroxide and sodium hydroxide = 1:2-4, wherein the mass ratio of potassium hydroxide and sodium hydroxide is 1:2. Potassium hydroxide and sodium hydroxide are strong bases and pore formers. At the activation pore-forming temperature, they can form oxides and metal carbonates with carbon elements. Under this ratio, the size and uniformity of the pore size can be controlled. When the ratio of carbon powder to strong base pore former is high or low, the pore structure of the carbon powder will be significantly affected, which directly affects its performance as an electrode material. By precisely controlling the alkali-carbon ratio, activated carbon with a specific pore size distribution and specific surface area can be prepared, thereby meeting the performance requirements of lithium battery negative electrode materials.
[0017] In some embodiments of the present invention, in step S4, the activation pore-forming conditions are: in a nitrogen atmosphere, the heating rate is 5-10°C / min, and the temperature is kept at 700°C-1000°C for 3-5h. Under this condition, the pore specific surface area can be increased and the pore structure can be improved. During the high-temperature reaction, tiny holes and pore walls will be generated, and these holes and pore walls can increase the specific surface area of the carbon material. Since the activation pore-forming conditions will generate holes and pore walls during the high-temperature reaction, the pore size distribution of the prepared carbon material is more uniform.
[0018] In some embodiments of the present invention, in step S5, the mixed acid solution is a mixture of hydrochloric acid and acetic acid, and according to the mass volume ratio, the activated material (g): mixed acid (ml) = 1: 0.5-2; the concentration of the mixed acid solution (hydrochloric acid + acetic acid) is 2-5%. The acidification treatment conditions further regulate the surface properties of the carbon powder. By introducing an acidic environment, the basic functional groups on the surface of the carbon powder can be neutralized or changed, thereby affecting its adsorption performance and chemical stability. Acidification treatment can remove or change the basic functional groups on the surface of the carbon powder, such as amino and thiol groups, which may be excessively generated during the strong base activation process, affecting the performance of the carbon powder. Through acidification treatment, the amount and type of these functional groups can be accurately controlled to achieve the purpose of optimizing the performance of the carbon powder. Intercalated potassium (K-GICs) is generated by reacting with the carbon in the carbon powder, which effectively promotes the development of the pore structure of the activated carbon. When the carbon powder is activated by strong alkali, if the ratio of the acidified solution is too high, it may cause the instability of K-GICs, and then deintercalation may occur, resulting in the deintercalation of K-GICs, which will affect the pore structure and surface properties of the activated carbon. If the ratio of the mixed acid is too low, the strong alkaline substances may not be completely neutralized, and these residual alkaline substances may affect the performance stability of the carbon powder; if the ratio of the mixed acid is too low, it may also affect the hardness of the carbon powder, thereby reducing its mechanical strength and stability. This may cause the carbon powder to break or deform in structure during use, affecting its use effect; in addition, if the ratio of the mixed acid is too low, it may not be able to completely adjust the chemical properties of the carbon powder, so that it maintains its original alkalinity or changes its surface chemical properties, which may affect its performance in specific applications. Therefore, controlling the appropriate ratio of the mixed acid is crucial to ensuring the performance and application effect of the carbon powder. In the step S5, the optimal ratio of the mixed acid is determined according to the specific needs and the purpose of the use of the carbon powder to ensure the performance and stability of the carbon powder.
[0019] In some embodiments of the present invention, in step S5, the drying temperature is 110° C.-150° C., and the moisture content after drying is ≦2.0%.
[0020] In some embodiments of the present invention, in step S5, the heating and acidification conditions are heating to 80-105° C. and keeping the temperature for 2-4 hours.
[0021] In some embodiments of the present invention, in step S2, the particle size of the carbon powder is 200-500 mesh.
[0022] On the other hand, an embodiment of the present invention provides a porous carbon from Cornus officinalis core, which is prepared by the above preparation method.
[0023] In a third aspect, an embodiment of the present invention provides an application of porous carbon from Cornus officinalis fruit core for preparing a negative electrode for a lithium battery.
[0024] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects:
[0025] The porous carbon prepared by the preparation method of the present invention has the following characteristics: 1. The particle size is moderate, so that the silicon nanoparticles can be evenly distributed in the pores of the porous carbon. At the same time, the silicon-carbon material produced by vapor deposition has uniform components and maintains a certain structural stability. 2. The particle size distribution is uniform, which can ensure that the silicon source gas can be evenly deposited in the pores of the carbon skeleton during high-temperature pyrolysis to form evenly distributed silicon nanoparticles. This helps to improve the overall performance of the silicon-carbon composite material, such as electrical conductivity and mechanical strength. 3. The pore size distribution of the porous carbon is uniform, which can provide sufficient space to buffer the volume change of nano-silicon during the charging and discharging process, thereby reducing the expansion rate and improving the cycle stability.
[0026] When preparing the porous carbon of the present invention, the cornus fruit core is first carbonized, and carbon powder is formed after grinding, which is then mixed with potassium hydroxide and sodium hydroxide and pores are formed in an activation furnace. Potassium hydroxide and sodium hydroxide, as strong alkalis, can effectively react with carbon in the carbon powder, erode part of the carbon atoms and generate corresponding metal carbonates and oxides. Subsequent acidification and washing can remove the generated metal carbonates and oxides, thereby forming pores. Through this method, the porous carbon formed has a moderate pore size, a large number of mesopores and macropores, and a small number of micropores; and the pore size distribution is uniform. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 These are SEM images of the porous carbon in Example 1 of the present invention at different magnifications. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0030] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other. The present invention will be described in detail below with reference to specific embodiments.
[0031] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0032] Example 1
[0033] The porous carbon of this embodiment was prepared as follows:
[0034] S1, drying the washed cornus fruit core at 110±1° C., and then putting it into a carbonization furnace for carbonization, and controlling the heating rate of the carbonization furnace to 2±0.5° C. / min under a nitrogen atmosphere, and after heating to 500±0.5° C., keeping the temperature at this temperature for 4 hours, thereby obtaining a carbonized cornus fruit core material;
[0035] S2, crushing and grinding the carbonized material of Cornus officinalis kernel obtained in step S1, passing through a 500-mesh sieve, further crushing the part above the sieve, and the part below the sieve is the carbon powder;
[0036] S3, mixing potassium hydroxide and sodium hydroxide in a mass ratio of 1:2 to obtain an alkaline mixture, and then placing the carbon powder in step S2 into the alkaline mixture in a mass ratio of 1:2 to the mixture, and stirring to obtain a mixture;
[0037] S4, placing the mixture of step S3 in an activation furnace, under a nitrogen atmosphere, controlling the activation furnace heating rate to 8±0.5°C / min, heating to 800±1°C, and then keeping the temperature at this temperature for 4h to perform activation and pore formation to obtain an activated material;
[0038] S5, placing the activated material of step S4 in a mixed acid solution at a mass volume ratio of activated material (g): mixed acid solution (ml) = 1:1, heating to 100±1°C, keeping warm for 3h, carrying out acidification reaction to remove impurities such as iron and potassium in the material; then filtering, repeatedly washing with pure water for multiple times, the pH value of the washing filter residue is about 6-7, washing, and then drying at 110±1°C until the moisture content of the material is ≦2.0%; then placing in a demagnetizer for demagnetization treatment to obtain porous carbon.
[0039] The mixed acid solution is prepared by mixing hydrochloric acid with a mass percentage of 31% and acetic acid with a concentration of 99.9% in a volume ratio of 1:4, and its acid concentration is 2%.
[0040] Example 2
[0041] The porous carbon of this embodiment was prepared as follows:
[0042] S1, drying the washed cornus fruit core at 105°C±1°C, and then putting it into a carbonization furnace for carbonization. Under a nitrogen atmosphere, the heating rate of the carbonization furnace is controlled to be 5±0.5°C / min. After the temperature is raised to 300±0.5°C, the temperature is kept at this temperature for 5 hours to obtain a carbonized cornus fruit core material;
[0043] S2, crushing and grinding the carbonized material of Cornus officinalis kernel obtained in step S1, passing through a 400-mesh sieve, further crushing the part above the sieve, and the part below the sieve is carbon powder;
[0044] S3, mixing potassium hydroxide and sodium hydroxide in a mass ratio of 1:2 to obtain an alkaline mixture, and then placing the carbon powder in step S2 into the alkaline mixture in a mass ratio of 1:2 to the mixture, and stirring to obtain a mixture;
[0045] S4, placing the mixture of step S3 in an activation furnace, under a nitrogen atmosphere, controlling the activation furnace heating rate to 5±0.5°C / min, heating to 700±1°C, and then keeping the temperature for 5h to perform activation and pore formation to obtain an activated material;
[0046] S5, placing the activated material of step S4 in a mixed acid solution at a mass volume ratio of activated material (g): mixed acid solution (ml) = 1:1, heating to 80±1°C, keeping the temperature for 4 hours, carrying out an acidification reaction to remove impurities such as iron and potassium in the material; then filtering, repeatedly washing with pure water for multiple times, the pH value of the washing filter residue is about 6-7, washing, and then drying at 110±1°C until the moisture content of the material is ≦2.0%; then placing in a demagnetizer for demagnetization treatment to obtain porous carbon.
[0047] The mixed acid solution is prepared by mixing hydrochloric acid with a mass percentage of 31% and acetic acid with a concentration of 99.9% in a volume ratio of 1:4, and its acid concentration is 2%.
[0048] Example 3
[0049] The porous carbon of this embodiment was prepared as follows:
[0050] S1, drying the washed cornus fruit core at 130±1° C., and then putting it into a carbonization furnace for carbonization, and controlling the heating rate of the carbonization furnace to 5±0.5° C. / min under a nitrogen atmosphere, and after heating to 600±0.5° C., keeping the temperature at this temperature for 3 hours, thereby obtaining a carbonized cornus fruit core material;
[0051] S2, crushing and grinding the carbonized material of Cornus officinalis kernel obtained in step S1, passing through a 500-mesh sieve, further crushing the part above the sieve, and the part below the sieve is the carbon powder;
[0052] S3, mixing potassium hydroxide and sodium hydroxide in a mass ratio of 1:2 to obtain an alkaline mixture, and then placing the carbon powder in step S2 into the alkaline mixture in a mass ratio of 1:2 to the mixture, and stirring to obtain a mixture;
[0053] S4, placing the mixture of step S3 in an activation furnace, under a nitrogen atmosphere, controlling the activation furnace heating rate to be 10±0.5°C / min, heating to 1000±1°C, and then keeping the temperature at this temperature for 3h to perform activation and pore formation to obtain an activated material;
[0054] S5, placing the activated material of step S4 in a mixed acid solution at a mass volume ratio of activated material (g): mixed acid solution (ml) = 1:0.5, heating to 105±1°C, keeping the temperature for 2h, carrying out an acidification reaction to remove impurities such as iron and potassium in the material; then filtering, repeatedly washing with pure water for multiple times, the pH value of the washed filter residue is about 6-7, washing, and then drying at 110±1°C until the moisture content of the material is ≦2.0%; then placing in a demagnetizer for demagnetization treatment to obtain porous carbon.
[0055] The mixed acid solution is prepared by mixing hydrochloric acid with a mass percentage of 31% and acetic acid with a concentration of 99.9% in a volume ratio of 1:4, and its acid concentration is 2%.
[0056] Example 4
[0057] The porous carbon of this embodiment was prepared as follows:
[0058] S1, drying the washed cornus fruit core at 130° C., and then putting it into a carbonization furnace for carbonization, and controlling the heating rate of the carbonization furnace to 5±0.5° C. / min under a nitrogen atmosphere, and after heating to 600±0.5° C., keeping the temperature at this temperature for 4 hours, thereby obtaining a carbonized cornus fruit core material;
[0059] S2, crushing and grinding the carbonized material of Cornus officinalis kernel obtained in step S1, passing through a 500-mesh sieve, further crushing the part above the sieve, and the part below the sieve is the carbon powder;
[0060] S3, mixing potassium hydroxide and sodium hydroxide in a mass ratio of 1:4 to obtain an alkaline mixture, and then placing the carbon powder in step S2 into the alkaline mixture in a mass ratio of the carbon powder to the mixture of 1:2, and stirring to obtain a mixture;
[0061] S4, placing the mixture of step S3 in an activation furnace, under a nitrogen atmosphere, controlling the activation furnace heating rate to 8±0.5°C / min, heating to 800±1°C, and then keeping the temperature at this temperature for 4h to perform activation and pore formation to obtain an activated material;
[0062] S5, placing the activated material of step S4 in a mixed acid solution at a mass volume ratio of activated material (g): mixed acid solution (ml) = 1:2, heating to 100±1°C, keeping the temperature for 3h, carrying out an acidification reaction to remove impurities such as iron and potassium in the material; then filtering, repeatedly washing with pure water for multiple times, the pH value of the washing filter residue is about 6-7, washing, and then drying at 110±1°C until the moisture content of the material is ≦2.0%; then placing in a demagnetizer for demagnetization treatment to obtain porous carbon.
[0063] The mixed acid solution is prepared by mixing hydrochloric acid with a mass percentage of 31% and acetic acid with a concentration of 99.9% in a volume ratio of 1:4, and its acid concentration is 2%.
[0064] Example 5
[0065] The porous carbon of this embodiment was prepared as follows:
[0066] S1, drying the washed cornus fruit core at 130±1° C., and then putting it into a carbonization furnace for carbonization, and controlling the heating rate of the carbonization furnace to 2±0.5° C. / min under a nitrogen atmosphere, and after heating to 500±0.5° C., keeping the temperature at this temperature for 4 hours, thereby obtaining a carbonized cornus fruit core material;
[0067] S2, crushing and grinding the carbonized material of Cornus officinalis kernel obtained in step S1, passing through a 500-mesh sieve, further crushing the part above the sieve, and the part below the sieve is the carbon powder;
[0068] S3, mixing potassium hydroxide and sodium hydroxide in a mass ratio of 1:3 to obtain an alkaline mixture, and then placing the carbon powder in step S2 into the alkaline mixture in a mass ratio of the carbon powder to the mixture of 1:2, and stirring to obtain a mixture;
[0069] S4, placing the mixture of step S3 in an activation furnace, under a nitrogen atmosphere, controlling the activation furnace heating rate to 8±0.5°C / min, heating to 800±1°C, and then keeping the temperature at this temperature for 4h to perform activation and pore formation to obtain an activated material;
[0070] S5, placing the activated material of step S4 in a mixed acid solution at a mass volume ratio of activated material (g): mixed acid solution (ml) = 1:2, heating to 100±1°C, keeping the temperature for 3h, carrying out an acidification reaction to remove impurities such as iron and potassium in the material; then filtering, repeatedly washing with pure water for multiple times, the pH value of the washing filter residue is about 6-7, washing, and then drying at 110±1°C until the moisture content of the material is ≦2.0%; then placing in a demagnetizer for demagnetization treatment to obtain porous carbon.
[0071] The mixed acid solution is prepared by mixing hydrochloric acid with a mass percentage of 31% and acetic acid with a concentration of 99.9% in a volume ratio of 1:4, and its acid concentration is 2%.
[0072] Comparative Example 1
[0073] The difference from Example 1 is that in this comparative example, the carbonization furnace in step S1 has a heating rate of 10°C / min and is kept at 800°C for 4 hours. The remaining steps are the same as in Example 1.
[0074] Comparative Example 2
[0075] The difference from Example 1 is that in this comparative example, the heating rate of the activation furnace in step S4 is 20°C / min, and the temperature is kept at 500°C for 4 hours. The remaining steps are the same as in Example 1.
[0076] Comparative Example 3
[0077] The difference from Example 1 is that in this comparative example, in step S3, the mass ratio of carbon powder to the mixture of potassium hydroxide and sodium hydroxide is 1:5, and the remaining steps are the same as in Example 1.
[0078] Comparative Example 4
[0079] The difference from Example 1 is that in this comparative example, in step S5, the mass ratio of activated material to mixed acid solution is 1:3, and the concentration of the mixed acid solution is 10%. The remaining steps are the same as in Example 1.
[0080] Experimental example
[0081] 1. The microstructure of the porous carbon of Example 1 was observed by scanning electron microscopy. Figure 1 As shown, Figure 1 The ad in the figure are microscopic images at different magnifications. Figure 1 It can be seen from (c and d) that the porous carbon particles of Example 1 have uniform particle size distribution and are of moderate size.
[0082] 2. Using the porous carbon of Examples 1-5 and Comparative Examples 1-4 as the skeleton, and graphite as the skeleton, the prepared porous carbon is placed in a gas phase rotary kiln for vapor deposition by a vapor deposition method. By increasing the temperature, introducing silane and carrier gas, and keeping the temperature, the in-situ composite of nano-silicon on the porous carbon matrix is achieved. Continue to increase the temperature, introduce a pyrolytic carbon source and a carrier gas, and keep the temperature to achieve pyrolytic carbon coating. After completing the above steps, cool to room temperature, and the silicon-carbon negative electrode material is obtained by discharging the material. Then mix it with graphite, wherein the silicon-carbon material accounts for 5-10% and the graphite accounts for 90%-95%, to obtain a lithium battery negative electrode. The negative electrode current collector material used in the lithium battery is metallic copper. Then assemble it into a lithium battery, and test the specific capacity of the lithium battery. The results are shown in Tables 1 and 2;
[0083] Table 1 Performance of negative electrode slurries and electrodes with different skeletons
[0084] Particle size (μm) <![CDATA[Specific surface area (m 2 / g)]]> Specific capacity (mAh / g) Graphite anode material 5-10 5 370 Silicon Carbon Anode Material 5-10 5 2000
[0085] In the above Table 1, the silicon-carbon negative electrode material is a silicon-carbon negative electrode material prepared by the above method with the porous carbon of Example 1 as the skeleton; and the graphite negative electrode material is a graphite negative electrode material prepared by the above method with graphite as the skeleton. The particle sizes of the two negative electrode materials are both within 5-10 μm, and the specific surface areas are the same, but after the two negative electrode materials are prepared into lithium batteries, the specific capacities of the lithium batteries are quite different. The silicon-carbon negative electrode material prepared by the porous carbon skeleton of Example 1 has a uniform pore size distribution of the porous carbon, which can provide sufficient space to buffer the volume change of nano-silicon during the charge and discharge process, thereby reducing the expansion rate and improving the cycle stability.
[0086] Table 2 Porous carbon and lithium battery performance of Examples 1-5 and Comparative Examples 1-4
[0087] Particle size (μm) <![CDATA[Specific surface area (m 2 / g)]]> Pore volume First charge and discharge efficiency (%) Example 1 5-8 1900 0.77 93 Example 2 5-8 1600 0.90 89 Example 3 5-8 1850 0.79 92 Example 4 5-8 1700 0.78 90 Example 5 5-8 1750 0.80 90 Comparative Example 1 5-8 1600 0.67 81 Comparative Example 2 5-8 1300 0.69 79 Comparative Example 3 5-8 1550 0.68 82 Comparative Example 4 5-8 1400 0.65 80
[0088] It can be concluded from Table 2 that the porous carbon of Examples 1-5 of the present invention has a particle size between 5-8 μm and a specific surface area larger than that of Comparative Examples 1-4, indicating that the porous carbon of Examples 1-5 has a large number of pores and can carry more silicon. Its pore volume is also larger than that of Comparative Examples 1-4, and its first charging efficiency is excellent.
[0089] In summary, the porous carbon provided by the embodiment of the present invention has a moderate particle size, which can enable silicon nanoparticles to be evenly distributed in the pores of the porous carbon. At the same time, the silicon-carbon material produced by vapor deposition has uniform components and maintains a certain structural stability. The uniform particle size distribution can ensure that the silicon source gas can be evenly deposited in the pores of the carbon skeleton during high-temperature pyrolysis to form evenly distributed silicon nanoparticles. It helps to improve the overall performance of silicon-carbon composite materials, such as conductivity and mechanical strength. The pore size distribution of porous carbon is uniform, and the pore size is less than 2nm, which can provide sufficient space to buffer the volume change of nano-silicon during the charging and discharging process, thereby reducing the expansion rate and improving the cycle stability.
[0090] The preparation method provided by the present invention is to firstly carbonize the kernel of Cornus officinalis, and then form carbon powder after grinding, and then mix it with potassium hydroxide and sodium hydroxide, and form pores in an activation furnace. Potassium hydroxide and sodium hydroxide, as strong alkalis, can effectively react with carbon in the carbon powder, erode part of the carbon atoms and generate corresponding metal carbonates and oxides, and then the subsequent acidification and washing can remove the generated metal carbonates and oxides, thereby forming pores; the key technology for preparing the porous carbon skeleton is reflected in the carbonization temperature, the type and proportion of the activator, etc. The high or low carbonization temperature determines the graphitization degree of the carbon material and the development of the pore structure; the type and proportion of the activator affect the specific surface area and pore size distribution of the porous carbon. In addition, by controlling the heating rate, the insulation temperature and the time during carbonization and pore formation, the pore size and the particle size can be controlled, so that the pore size of the porous carbon formed is moderate, the number of mesopores and macropores is large, the number of micropores is small; and the pore size distribution is uniform.
[0091] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing porous carbon from cornus fruit core, characterized in that: The steps include: S1, drying the washed cornus fruit pits at 105° C.-130° C., and then putting them into a carbonization furnace for carbonization to obtain a carbonized cornus fruit pit material; S2, crushing and grinding the carbonized material of Cornus officinalis kernel obtained in step S1 to obtain carbon powder; S3, placing the carbon powder in step S2 into a mixture of solid potassium hydroxide and solid sodium hydroxide, and stirring the mixture to obtain a mixture; S4, placing the mixture of step S3 in an activation furnace for activation and pore formation to obtain an activated material; S5, placing the activated material in step S4 in a mixed acid solution, heating it for acidification reaction, then filtering, washing the filter residue, drying it, and demagnetizing it.
2. The method for preparing porous carbon from cornus fruit core according to claim 1, characterized in that: In step S1, the carbonization conditions are: in a nitrogen atmosphere, the heating rate is 2-5°C / min, and the temperature is kept at 300°C-600°C for 3-5h.
3. The method for preparing porous carbon from cornus fruit core according to claim 1, characterized in that: In the step S3, the mass ratio is carbon powder: the total amount of potassium hydroxide and sodium hydroxide = 1:2-4, wherein the mass ratio of potassium hydroxide to sodium hydroxide is 1:
2.
4. The method for preparing porous carbon from cornus fruit core according to claim 1, characterized in that: In step S4, the activation and pore-forming conditions are: in a nitrogen atmosphere, the heating rate is 5-10°C / min, and the temperature is kept at 700°C-1000°C for 3-5h.
5. The method for preparing porous carbon from cornus fruit core according to claim 1, characterized in that: In step S5, the mixed acid solution is a mixture of hydrochloric acid and acetic acid, and the mass volume ratio is activation material (g): mixed acid (ml) = 1:0.5-2; the concentration of the mixed acid solution is 2-5%.
6. The method for preparing porous carbon from cornus fruit core according to claim 1, characterized in that: In the step S5, the drying temperature is 110° C.-150° C., and the moisture content after drying is ≦2.0%.
7. The method for preparing porous carbon from cornus fruit core according to claim 1, characterized in that: In step S5, the conditions for heating and acidification are heating to 80-105° C. and keeping the temperature for 2-4 hours.
8. The method for preparing porous carbon from cornus fruit core according to claim 1, characterized in that: In the step S2, the particle size of the carbon powder is 200-500 meshes.
9. A porous charcoal made from cornus fruit core, characterized in that: Prepared by the method described in any one of claims 1 to 8.
10. An application of porous carbon from cornus fruit core, characterized in that: The porous carbon is prepared by the method according to any one of claims 1 to 8 and is used to prepare the negative electrode of a lithium battery.
Citation Information
Patent Citations
Preparation method of dogwood kernel active carbon
CN106395818A
